Formulation and Optimization of Polyherbal Fast Dissolving Tablet of Curcumin, Quercetin and Rutin (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current study was focused on the design, development, and evaluation of the fast-dissolving tablet of a polyherbal combination of curcumin, quercetin, and rutin. These herbal drugs are poorly water-soluble. The center of attention for this study is to provide quick onset of action, improved bioavailability, and increased patient compliance for administering a tablet. All parameters of Polyherbal Fast dissolving tablets were evaluated, and all were found within the official range. Drug content ranges between 90 to 105%. The formulation PHT24 containing a high concentration of Crosspovidone enhanced the drug release up to 94% within 5 minutes compared with the control. The optimized formula PHT24 showed favorable drug dissolve characteristics with better mouth feel and acceptable fast-dissolving properties. It was also observed that all formulations were acceptable with reasonable limits of the standard required for fast-dissolving tablets. The study also reveals that the Superdisintegrants used were effective in low or high concentrations. It was concluded that fast dissolving tablets with enhanced dissolution rates could be made using selected Superdisintegrants.